Construction of network entrepreneurial platform leadership characteristics model: based on the grounded theory - Pan, Jianlin; Lin, Jie (Journal of Business Economics and Management, 2019)
With the embedding of internet technology, the entrepreneurial model has been gradually developing from  traditional single linear channel into network platform with symbiotic multi-platform. Platform leadership is the most important part of the new one and has been caught greatest attention. This paper put forward a new conception of network entrepreneurial platform leadership innovatively. By the integrated use of the Classical Grounded theory, the Procedure Grounded Theory and the Construction Grounded Theory, it adopted the normative research process of open coding, axial coding and selective coding to refine 34 concept—multi-node interactive, cross-level coupling relationship, etc, and formed  11 fundamental categories which include platform leadership power, network organization entrepreneurial mode, etc. Then, we analyzed the interactions between categories, based on which, a double-level and three-type-characteristics model were ultimately built. The study was finished by both two methods of statistical software and manual operation. In order to improve the reliability and validity of the study, it invited another coder to test the category subordination collaboratively, and used matched group to test the theoretical saturation.